2010
DOI: 10.1007/s00253-010-2606-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the antimicrobial peptide cecropin fused with human lysozyme in Escherichia coli

Abstract: Lysozyme is an abundant, cationic antimicrobial protein that plays an important role in host defense. It targets the beta (1-4) glycosidic bond between N-acetylglucosamine and N-acetylmuramic residues that make up peptidoglycan, making lysozyme highly active against Gram-positive bacteria. However, lysozyme alone is inactive against Gram-negative bacteria because it cannot reach the peptidoglycan layer. Cecropins are cationic molecules with a wide range of antimicrobial activities. The main target for these pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Microbicidal assay was performed as previously described (Ueno et al 2010;Lu et al 2010). Each bacterial strain was cultured to exponential phase and diluted 1,000 times with LB culture medium.…”
Section: Microbicidal Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Microbicidal assay was performed as previously described (Ueno et al 2010;Lu et al 2010). Each bacterial strain was cultured to exponential phase and diluted 1,000 times with LB culture medium.…”
Section: Microbicidal Assaymentioning
confidence: 99%
“…To address this issue, numerous biological expression systems have been established to produce AMPs in hosts such as prokaryotic cells and yeast cells (Jin et al 2006;Xu et al 2007;Chen et al 2009;Lu et al 2010). However, each of these systems presents their own set of problems.…”
Section: Introductionmentioning
confidence: 99%
“…Evidences of synergism between lysozyme and cecropin have generated interest to design novel antimicrobial protein with a broader spectrum of activity and increased potency [23]. Therefore, it is necessary to efficiently express recombinant antimicrobial peptide parasin I fused with human lysozyme in yeast expression system.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) They are able to form specific amphipathic alpha-helices, which allow them to target nonpolar lipid cell membranes, and have strong antibiotic activity against both Gram-positive and Gram-negative bacteria at low micromolar concentrations. 3,4) More recent studies have also indicated the antitumor activity of cecropins against various cancer cell lines of leukemia, lymphoma, colon carcinoma, small cell lung cancer and gastric cancer, but without damage to human normal cells which would make it a good candidate for the development of anti-tumor agents. 5,6) The Musca domestica gene cecropin (GenBank accession number: EF175878) was cloned in our laboratory from the larva.…”
mentioning
confidence: 99%